2021
DOI: 10.1021/acs.chemmater.1c02584
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Thermoelectric Properties in the Triple Cation Zintl Phase: Yb13–xCaxBaMgSb11 (x = 1–6)

Abstract: The band structure of Yb14MgSb11 is tuned by substituting the more earth-abundant cations, Ca and Ba, on the four crystallographically distinct Yb sites (Yb13–x Ca x BaMgSb11 (x = 1, 2, 3, 4, 5, 6)). Single crystals of composition Yb9.7(2)Ca3.85(5)Ba0.29(4)Mg1.13(3)Sb11.0(1) were grown from Sn flux revealing the cation site preferences. Magnetic measurements on this crystal show paramagnetic behavior consistent with the presence of ∼0.85 Yb3+. High-purity samples (>98%) with compositions close to nominal of Yb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…9 After this point phonon scattering dominates, and there is a decrease in the thermal conductivity to a minimum of 7.7 mW cm −1 K −1 at 1073 K. As the temperature increases, there is an upturn in the thermal conductivity which corresponds to the onset of bipolar conduction and an increase electronic contribution due to the activation of minority carriers. 9,11,24,25 This agrees well with previously reported thermal conductivities of polycrystalline samples of Yb 14 MnSb 11 made from both elemental and binary precursors. 11,12 The temperature-dependent behavior of this sample (x = 0.9) is distinct and likely a result of increased contributions from the larger amounts of LuSb impurity seen in both PXRD and SEM.…”
Section: S Y N T H E S I S a N D P H A S E P U R I T Y S A M P L E S...supporting
confidence: 91%
See 2 more Smart Citations
“…9 After this point phonon scattering dominates, and there is a decrease in the thermal conductivity to a minimum of 7.7 mW cm −1 K −1 at 1073 K. As the temperature increases, there is an upturn in the thermal conductivity which corresponds to the onset of bipolar conduction and an increase electronic contribution due to the activation of minority carriers. 9,11,24,25 This agrees well with previously reported thermal conductivities of polycrystalline samples of Yb 14 MnSb 11 made from both elemental and binary precursors. 11,12 The temperature-dependent behavior of this sample (x = 0.9) is distinct and likely a result of increased contributions from the larger amounts of LuSb impurity seen in both PXRD and SEM.…”
Section: S Y N T H E S I S a N D P H A S E P U R I T Y S A M P L E S...supporting
confidence: 91%
“…The thermal conductivity of the sample of Yb 14 MnSb 11 begins at 8.4 mW cm –1 K –1 at room temperature and increases to a maximum of 8.9 mW cm –1 K –1 at 573 K due to an increase in electronic contribution as carriers move between the bands of the complex structure . After this point phonon scattering dominates, and there is a decrease in the thermal conductivity to a minimum of 7.7 mW cm –1 K –1 at 1073 K. As the temperature increases, there is an upturn in the thermal conductivity which corresponds to the onset of bipolar conduction and an increase electronic contribution due to the activation of minority carriers. ,,, This agrees well with previously reported thermal conductivities of polycrystalline samples of Yb 14 MnSb 11 made from both elemental and binary precursors. , The temperature-dependent behavior of this sample ( x = 0.9) is distinct and likely a result of increased contributions from the larger amounts of LuSb impurity seen in both PXRD and SEM. LuSb is also seen in the PXRD and SEM for x = 0.7 at lesser amounts and may explain the trend of increasing thermal conductivity at x = 0.7 and 0.9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An improved synthetic route is shown to allow for efficient synthesis of stoichiometric and extremely high-purity products. Through this synthesis, a sample of Yb 14 MgSb 11 was produced, which exhibited the material leading efficiencies of zT = 1.28 at 1175 K. The slight improvement to overall zT increased the zT avg of Yb 14 MgSb 11 in the temperature window 875 to 1275 K from 1.10 to 1.15, making this phase competitive with Yb 14 MnSb 11 (1.07). ,, The increase in average zT is important when considering these materials for incorporation into high-temperature thermoelectric generators, such as a radioisotope thermoelectric generator (RTG). The impact of the experimental method in acquiring the Seebeck coefficient was also investigated and showed that while the commercial four-probe experimental setup provides reliable electrical resistivity; Seebeck coefficients are exaggerated due to a cold-finger effect at high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the conversion efficiency and output power of thermoelectric generators depends on the temperature difference across the thermoelectric compounds, 5–8 identifying novel materials with high ZT values and high melting points is also of particular interest. However, to date, only a handful of compounds are able to operate above 1000 K; a restricted list that includes the state-of-the-art Si–Ge alloys, 9,10 Zintl phases based on Yb 14 MnSb 11 and RE 3− x Te 4 (RE = La, Nd, Pr, Gd), 11–17 and half-Heusler alloys. 18–20…”
Section: Introductionmentioning
confidence: 99%